Answer:
let's see what to do buddy...
Explanation:
We have this equation to find the distance between two points :
a = ( 2 , 0 ) and b = ( -4 , 6 )
![distance = \sqrt{ {( \: y(b) - y(a) \: })^(2) + ( \: {x(b) - x(a)} \: )^(2) } \\](https://img.qammunity.org/2021/formulas/mathematics/high-school/h2pide59ie9dn0sxzmc1vr8myg0cthps45.png)
Now just need to put the coordinates in the equation :
![distance = \sqrt{ ({6 - 0})^(2) + ({ - 4 - 2})^(2) } \\ distance = \sqrt{ {6}^(2) + ({ - 6})^(2) } = √(36 + 36) \\ distance = √(36 * 2) = 6 √(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/g6yo4jc36m58uzbel7w55614isf43wf9kb.png)
And we're done.
Thanks for watching buddy good luck.
♥️♥️♥️♥️♥️